Five new species and one new record of the genus Phaenocarpa Foerster (Hymenoptera, Braconidae, Alysiinae) from South Korea - Ju-Hyeong Sohn; Cornelis van Achterberg; Sangjin Kim; Hyojoong Kim (ZooKeys, 2024)
Five new species of the genus Phaenocarpa Foester, 1863 (Braconidae: Alysiinae) are described and illustrated: P. acutidentata Sohn & van Achterberg, sp. nov., P. tacitoides Sohn & van Achterberg, sp. nov., P. setosa Sohn & van Achterberg, sp. nov., P. tanycauda Sohn & van Achterberg, sp. nov., and P. angusticeps Sohn & van Achterberg, sp. nov. Additionally, P. tacita Stelfox, 1941 is recorded for the first time from South Korea. The barcode region of mitochondrial cytochrome c oxidase I (COI) was also analyzed for the seven congeneric species including one from GenBank. In addition, an identification key for the Phaenocarpa species recorded in Korea is provided.